Optimal DG Placement with the Aim of Profits Maximization - Sobhan Dorahaki (Institute of Advanced Engineering and Science, 2016)
Using distributed generation power plants is common due to advantages such as system capacity release, voltage support and reduced energy losses in power networks. Prior to the creation of distributed generation plants (DG), economic calculation is needed in order to find the optimum location. In this study, IEEE 57 bus test system is evaluated using two index of LMP and CP. Then, the optimal location of distributed generation plants is studied in experimental network. Finally, the effects of DG correct location on buses LMP after DG installation is studied.